PEMANFAATAN LIMBAH PETERNAKAN DALAM MENDUKUNG USAHA TANI HORTIKULTURA DI KEBAWETAN KEPAHIANG - Jafrizal -; Wismalinda Rita (DHARMA RAFLESIA, 2018)
Kabawetan sub-district is one of the central areas of plantation, agriculture and animal husbandry in the province of Bengkulu. In running their farm, farmers still use conventional system, especially the use of anorganic fertilizer (chemical factory) and overused pesticide. Besides as a farmer, almost in every village people also seek beef cattle and dairy cattle. Farm waste already started causing environmental problems for society, while on the other hand they have difficulty in getting the fertilizer for business continuity (horticultural crops). With input from the farmers, we agreed to offer a solution using animal waste into organic fertilizer. The form of such activities carry out: education and counseling about environmental friendly agriculture; as well as training in the making Bokashi and biourine. Later stage is making plots experiment to apply organic fertilizer produced vegetable plants. This community service activity has been done and able to reduce farmers' dependence on chemical fertilizers and chemical pesticides, and also revive local knowledge in farming. From the aspect of production, horticultural products (vegetables) produced by farmers are more environmental friendly. Keywords: Horticulture, Bokashi, Biourine, Organic Farming